Multidimensional free shape-morphing flexible neuromorphic devices with regulation at arbitrary points - Jiaqi Liu; Chengpeng Jiang; Qianbo Yu; Yao Ni; Cunjiang Yu; Wentao Xu (Nature Communications)
Abstract Biological neural systems seamlessly integrate perception and action, a feat not efficiently replicated in current physically separated designs of neural-imitating electronics. This segregation hinders coordination and functionality within the neuromorphic system. Here, we present a flexible device tailored for neuromorphic computation and muscle actuation. Each individual device component emulates essential synaptic functions for neural computing, while the collective ensemble replicates muscle actuation in response to efferent neuromuscular commands. These properties stem from densely-packed, hydrophilic nanometer-sized channels, and the erection of a high-entropy, intricately silver nanowires to capture and store of hydrated cations. Leveraging the remarkable deformation effect, we demonstrate hazard detection-avoidance robot, and multidimensional integration for arbitrary programmed shapes like 360° panoramic information capture and soft-bodied biological deformations wherein localized responses to stimuli are harmoniously integrated to achieve arbitrary coordinated motion. These results provide a significant avenue for the development of future flexible electronics and bio-inspired systems.